1993
DOI: 10.1159/000457553
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Paracetamol in the Neonate and Infant after Administration of Propacetamol Chlorhydrate

Abstract: The pharmacokinetic parameters of paracetamol were studied after 15 min intravenous infusion of 15 mg/kg of propacetamol (Prodafalgan®) in 5 neonates aged less than 10 days and 7 infants aged between 1 and 12 months. Blood was sampled at 0,0.5,2 and 6 h after the first intravenous infusion of propacetamol. The infants aged less than 10 days had higher plasma concentrations of paracetamol, a longer half-life (3.5 vs. 2.1 h) and a lower plasma clearance (0.149 vs. 0.365 l/h/kg) than the older children. Dose simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
2
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 1 publication
6
43
2
1
Order By: Relevance
“…In five neonates aged Ͻ10 days administered paracetamol (as propracetamol, a prodrug of paracetamol) clearance was found to be 2.5 ml/min./kg, compared with 6.1 ml/min./ kg for infants between 1-12 months (Autret et al 1993). Levy et al (1975) found a mean paracetamol half-life in 12 neonates aged Ͻ3 days of 3.5 hr, compared with 1.9-2.2 in adults .…”
Section: Paracetamolmentioning
confidence: 98%
“…In five neonates aged Ͻ10 days administered paracetamol (as propracetamol, a prodrug of paracetamol) clearance was found to be 2.5 ml/min./kg, compared with 6.1 ml/min./ kg for infants between 1-12 months (Autret et al 1993). Levy et al (1975) found a mean paracetamol half-life in 12 neonates aged Ͻ3 days of 3.5 hr, compared with 1.9-2.2 in adults .…”
Section: Paracetamolmentioning
confidence: 98%
“…Propacetamol is hydrolysed by plasma esterases so that 1 g of propacetamol is hydrolysed to 0.5 g paracetamol in adults 1820. Propacetamol bioavailability was compared with paracetamol.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…• Pharmacological therapy for ongoing pain 17,19,34,58,[71][72][73][74][75][76][77][78][79][80] ( Table 4). …”
Section: Management Of Pain In the Newbornmentioning
confidence: 99%